Advances on Bioanalysis - Barroso, Mário (2022)
Funding: This work is supported by projects UIDB/00709/2020 and UIDP/00709/2020 (CICS-UBI); UIDB/04378/2020 and UIDP/04378/2020 (Applied Molecular Biosciences Unit UCIBIO), LA/P/0140/2020 (i4HB) carried out by National Funds by Foundation for Science and Technology (FCT) and co-financed by community funds.